PENGARUH ORIENTASI PASAR, INOVASI PRODUK DAN KUALITAS LAYANAN TERHADAP KINERJA PEMASARAN DALAM UPAYA MENCAPAI KEUNGGULAN BERSAING - Wachjuni Wachjuni (Politeknik Sawunggalih Aji, 2017)
Market orientation , product innovation, and quality service is of great importance for the improvement of marketing performance in achieving competitive advantage. For to win this competition, the companies must be able to pay attention to customers and the ability of competitors so it can coordinate with the company's resources. From here, the company built the strategy include: product innovation through the development or creation of new products to consumers and customers and provide optimum service, so the company can create a competitive advantage over competitors. Keywords : Market orientation , product innovation, quality service, marketing performance, and competitive advantage